The point where most people fall with induction is, as Riviet and pLuvia have noted, where you need to use your assumption. Basically, say you have:
Prove 1 + 2 + 4 + 8 + ... + 2
n-1 = 2
n - 1 is true for all n≥1 by induction.
You know how to do the first two steps, and you end up with:
Assume true for n = k:
(1 + 2 + 4 + 8 + ... + 2k-1) = 2k - 1 [1]
Notice how you're saying: all the terms up to n = k is equal to 2
k - 1. Then, when you prove true for n = k + 1, you're trying to prove this:
(1 + 2 + 4 + 8 + ... + 2k-1) + 2
(k+1)-1 = 2
(k+1) - 1 [2]
Notice the bolded and bracketed part. We've already assumed that it equals 2
k - 1 (see equation [1]). So we substitute [1] straight into [2]:
Since (
1 + 2 + 4 + 8 + ... + 2k-1) = 2
k - 1 [1]
and
(1 + 2 + 4 + 8 + ... + 2k-1) + 2
(k+1)-1 = 2
(k+1) - 1 [2]
(
2k - 1) + 2
(k+1)-1 = 2
(k+1) - 1 (subbing [1] into [2])
From there it's manipulation:
LHS = 2
k - 1 + 2
k
= 2.2
k - 1
= 2
(k+1) - 1
= RHS
Therefore, since true for n=1 and true for n = k+1 if true for n=k, it is true for n≥1 by mathematical induction.
If you practise for a while on the straightforward ones, you'll get more used to the manipulating that you need to do to complete the harder induction questions. I hope that helps out.
I_F